2021
DOI: 10.1186/s11689-021-09375-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinography and contrast sensitivity, complementary translational biomarkers of sensory deficits in the visual system of individuals with fragile X syndrome

Abstract: Background Disturbances in sensory function are an important clinical feature of neurodevelopmental disorders such as fragile X syndrome (FXS). Evidence also directly connects sensory abnormalities with the clinical expression of behavioral impairments in individuals with FXS; thus, positioning sensory function as a potential clinical target for the development of new therapeutics. Using electroretinography (ERG) and contrast sensitivity (CS), we previously reported the presence of sensory defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
1
5
0
Order By: Relevance
“…For example, in Fragile X syndrome, a disorder strongly linked to ASD, symptoms include reduced temporal resolution of vision in infants (Farzin, Rivera, and Whitney 2011), lower contrast sensitivity (Kogan et al 2004), visual hypersensitivity (Raspa et al 2018), and sleep disturbances such as night waking (Hagerman et al 2017). Some of these symptoms are homologous in the mouse model of Fragile X syndrome, which supports the idea that “low level” retinal processing may shape symptoms (Saré et al 2017; Goel et al 2018; Perche et al 2021; Felgerolle et al 2019; Yang et al 2022).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, in Fragile X syndrome, a disorder strongly linked to ASD, symptoms include reduced temporal resolution of vision in infants (Farzin, Rivera, and Whitney 2011), lower contrast sensitivity (Kogan et al 2004), visual hypersensitivity (Raspa et al 2018), and sleep disturbances such as night waking (Hagerman et al 2017). Some of these symptoms are homologous in the mouse model of Fragile X syndrome, which supports the idea that “low level” retinal processing may shape symptoms (Saré et al 2017; Goel et al 2018; Perche et al 2021; Felgerolle et al 2019; Yang et al 2022).…”
Section: Introductionsupporting
confidence: 72%
“…1A ), where excitatory and inhibitory interneurons shape ganglion cells’ tuning for specific types of light information. Gross physiology of the human retina in people with ASD using electroretinography has revealed slower and lower amplitude responses of the optic nerve, suggesting that atypical visual processing in ASD begins in the retina (Perche et al 2021; Constable et al 2020). However, whether and how the function of individual types of retinal ganglion cells is altered in ASD has not, to our knowledge, been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, few studies focusing on Dark-Adapted (DA) conditions have also shown alteration in the b-wave amplitude (Constable et al, 2016). In parallel of these clinical works, preclinical data demonstrated that FMRP is expressed in all retinal layers (Rossignol et al, 2014;Guimaraes-Souza et al, 2016;Zhang et al, 2020) and that its total absence in young and adult Fmr1 KO mice (murine model of FXS) is associated to several protein deficits, neuronal immaturity, and thus to retinal functional alterations (Rossignol et al, 2014;Perche et al, 2018) as observed in human conditions (Perche et al, 2021). Moreover, retinal Fmrp content is dependent of light exposure, since studies showed higher levels of Fmrp RNA in retinas exposed to light when compared to DA retinas (Guimaraes-Souza et al, 2016).…”
Section: Short Communicationmentioning
confidence: 96%
“…Reduced FMRP expression has also been identified in other neurodevelopmental human disorders such as autism, schizophrenia, and bipolar disorder (Fatemi et al, 2010(Fatemi et al, , 2013(Fatemi et al, , 2013Fatemi et al, 2013a,b;Fernandez et al, 2013;Kelemen et al, 2013;Kovacs et al, 2013;Jacquemont et al, 2014). Interestingly, all FMRP deficits were associated with retinal function alteration characterized by electroretinogram (ERG) wave modifications (Constable et al, 2016(Constable et al, , 2020Hebert et al, 2017Hebert et al, , 2020Perche et al, 2021). Indeed, under Light-Adapted (LA) conditions, the absence of FMRP (Perche et al, 2021) or its downregulation (Hebert et al, 2015(Hebert et al, , 2017(Hebert et al, , 2020Constable et al, 2016Constable et al, , 2020 was linked to a decreased b-wave amplitude and prolonged latencies whereas delayed LA ERG response were described in specific cases.…”
Section: Short Communicationmentioning
confidence: 98%
See 1 more Smart Citation